Primer on social bonds and recent developments in Asia. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Social bonds are designed to raise proceeds for projects with positive social outcomes. The publication serves as a primer on how social bonds can facilitate more inclusive development and help in Asia recovery from COVID-19. It also identifies potential solutions to overcome salient barriers to social bond market development in the region.
Keywords: Finance -- Asia; Social bond -- Asia; Financial institution; Electronic book